2020
DOI: 10.22146/aij.v7i1.60389
|View full text |Cite
|
Sign up to set email alerts
|

Customer Decision Making Analysis in Choosing the eMarketplace which Provide Food Products

Abstract: Entering the digital era, shopping activities no longer have to go directly to the seller to get the desired product, including food products such as fast food, beverages, and variou s cooking needs. Currently customers can meet all their needs just simply by accessing a n e-marketplace application developed by the company to order the desired product and t hen the product will be delivered to the courier to the home or where the customer is loca ted. Until 2018 there are at least 10 e-marketplaces in Indonesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Responsiveness describes the quality of services, including complaint handling; assurance is the ability to assure consumers' security and privacy. In addition, Azali et al [4] found that platform emarketplace has 11 attributes that influence buying decisions: product search, reputation information, payment method, user data protection, location map, product quality, store search, product prices, ease to operate, product variations, and attractive display. Based on the references, this paper built 18 attributes that are attached to the digital platform of the convenience store can be seen in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Responsiveness describes the quality of services, including complaint handling; assurance is the ability to assure consumers' security and privacy. In addition, Azali et al [4] found that platform emarketplace has 11 attributes that influence buying decisions: product search, reputation information, payment method, user data protection, location map, product quality, store search, product prices, ease to operate, product variations, and attractive display. Based on the references, this paper built 18 attributes that are attached to the digital platform of the convenience store can be seen in Table 1.…”
Section: Methodsmentioning
confidence: 99%